2021
DOI: 10.23887/ijerr.v4i2.38388
|View full text |Cite
|
Sign up to set email alerts
|

Improving Science Learning Outcomes Through the SETS (Science Environment Technology And Society) Approach

Abstract: Science learning packaging still focuses on conventional learning. This causes students to feel bored in learning and have difficulty understanding the material taught by the teacher. This problem affects the students' low science learning outcomes. This study aims to analyze the significant differences in science learning outcomes for groups of students who are taught through the application of the SETS approach and students who are taught through conventional learning. This type of research is a quasi-experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…By making abstract concepts concrete and simplifying complex concepts, the use of visual media, modules, and guided-experiments books improved learning outcomes in terms of students' level of thinking. While Putra (2021) and Widiastuti and Purnawijaya (2021) only used the SETS approach without any additional strategies, the results showed that students still value science learning more than those in the non-SETS group. According to Poluakan et al (2020), in relation to STS approach subgroup, the teaching model stimulated students' interest in science learning, particularly with regard to enhancing scientific literacy, when used in conjunction with the social media platform, Facebook.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By making abstract concepts concrete and simplifying complex concepts, the use of visual media, modules, and guided-experiments books improved learning outcomes in terms of students' level of thinking. While Putra (2021) and Widiastuti and Purnawijaya (2021) only used the SETS approach without any additional strategies, the results showed that students still value science learning more than those in the non-SETS group. According to Poluakan et al (2020), in relation to STS approach subgroup, the teaching model stimulated students' interest in science learning, particularly with regard to enhancing scientific literacy, when used in conjunction with the social media platform, Facebook.…”
Section: Discussionmentioning
confidence: 97%
“…When each study was analyzed, STS approach had been to have a large and positive impact on students' critical thinking ability (Astuti et al, 2019;), scientific attitudes (Astuti et al, 2019;, interest in learning (Igboanugo, 2021;), ability to apply scientific concepts (Kapici et al, 2017), scientific learning (Poluakan et al, 2020, scientific literacy (Pratama et al, 2018;Prasasti & Listiani, 2019), scientific skills (Prasasti & Listiani, 2019), motivation (Priyambodo, Sukirno et al, 2021), and learning outcomes (Putra, 2021;Widiastuti & Purnawijaya, 2021). Medium effect sizes were observed in the studies of Budi et al (2018) and on students' critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This constructivism model emphasizes the application of the concept of learning by doing, namely students learn something through manual activities (Sumini et al, 2022;Widiastuti & Purnawijaya, 2021). Actions taken in an effort to improve cognitive abilities and student learning activities are taken by applying a constructivism approach (Witkowska-Tomaszewska, 2019;Gems et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…English education emphasizes giving students direct experience to develop competency for students who are able to understand and compose descriptive text. English education is directed toward "finding out and doing" so that it can help students gain a deeper understanding of descriptive material (Widiastuti & Purnawijaya, 2021). Therefore, the method applied in presenting English learning is to combine experience with English processes and understanding English products in the form of hands-on activities.…”
Section: Introductionmentioning
confidence: 99%